2016
DOI: 10.1002/psp.1953
|View full text |Cite
|
Sign up to set email alerts
|

Can Travelling Mothers Ever Arrive? Articulating Internal and International Migration within a Transnational Perspective of Care

Abstract: Tracing the continuously changing dynamics between China and its quasi-independent capitalist 'special territory', Hong Kong, this paper brings together the under-recognised cross-border caregivers and over-recognised care consumers in the wake of multiple care crises, articulating how internal and international migration clashes in the borderlands crossed by various kinds of travelling mothers from the Mainland. With a focus on care as social practices and relations, it observes how the boundary between inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Despite the geographical proximity between mainland China and Hong Kong and having the same ethnic background, immigrants from mainland China are often regarded by locally born Hong Kong residents as members of two distinctly different social groups (Huang, ; Newendorp, ; Ngo & Li, ). Antimigration advocates have increasingly constructed dress style, manners, language proficiency, and accents as symbolic boundaries to separate locals/“insiders” from immigrants/“outsiders” (Edgell & Tranby, , p. 177).…”
Section: Frequent Border‐crossing Children In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the geographical proximity between mainland China and Hong Kong and having the same ethnic background, immigrants from mainland China are often regarded by locally born Hong Kong residents as members of two distinctly different social groups (Huang, ; Newendorp, ; Ngo & Li, ). Antimigration advocates have increasingly constructed dress style, manners, language proficiency, and accents as symbolic boundaries to separate locals/“insiders” from immigrants/“outsiders” (Edgell & Tranby, , p. 177).…”
Section: Frequent Border‐crossing Children In Hong Kongmentioning
confidence: 99%
“…These parents regard the Hong Kong education system as more superior than China's because the former is believed to be providing a more globalised curriculum and offer training that will facilitate future upward mobility in a competitive labour market. Despite the geographical proximity between mainland China and Hong Kong and having the same ethnic background, immigrants from mainland China are often regarded by locally born Hong Kong residents as members of two distinctly different social groups (Huang, 2016;Newendorp, 2008;Ngo & Li, 2016). Antimigration advocates have increasingly constructed dress style, manners, language proficiency, and accents as symbolic boundaries to separate locals/"insiders" from immigrants/"outsiders" (Edgell & Tranby, 2010, p. 177).…”
Section: The Geographic Proximity Between Southern China and Hongmentioning
confidence: 99%
“…A growing body of research in recent years has observed and examined forms of migration variously named 'onward', 'stepwise' and 'multinational'. Accounts of onward and stepwise migration are not themselves particularly new, having been observed in internal migration for several decades (Keown, 1971;Withers and Watson, 1991) and aligning with established research on the connection between internal and international migration (Huang, 2016;Hugo, 2016). 'Multinational migration' is a more recent observation (Paul, 2017) and is taken to refer to 'the varied movements of international migrants across more than one overseas destination with significant time spent in each overseas country' (Paul and Yeoh, 2020: 2).…”
Section: Multinational Migrationmentioning
confidence: 99%
“…He notes that increased opportunities for migration and other forms of mobility for Chinese citizens has had the effect of undermining local authorities to the benefit of the central state and the ruling party apparatus. His argument dovetails with Huang's () piece, which documents how ongoing attempts by the Hong Kong authorities to maintain a measure of sovereignty within the ‘one state, two systems’ are partially played out through the regulations and discourses that both compel and curtail the constant ‘mobility’ of mainland women migrant ‘visitors’ in their interactions with the tangled bureaucracy of the Special Administrative Region.…”
Section: Rethinking the Gap: Constitutive Approaches To Theorising MImentioning
confidence: 99%
“…In larger countries, internal migration can take place at a scale analogous to international migration, with migrants moving across large geographic areas, in journeys that often involve traversing equally large cultural distances. That ‘internal’ migration may involve cultural dissonance is illustrated by Huang's () contribution in this issue, which investigates the movements of mainland Chinese women into the Hong Kong Special Administrative Region (HKSAR). Huang explores not only the legal and bureaucratic ‘in‐between‐ness’ of women negotiating ‘one country, two systems’ but also the ways in which these mainlanders find themselves culturally and linguistically ‘othered’ from the Cantonese ‘natives’.…”
Section: Rethinking the Gap: Constitutive Approaches To Theorising MImentioning
confidence: 99%